Comparative Evaluation of Prosopis cineraria (L.) Druce and Its ZnO Nanoparticles on Scopolamine Induced Amnesia - Yadav, Ekta; Singh, Deepika; Yadav, Pankajkumar; Verma, Amita (Frontiers in Pharmacology, 2018)
Over recent years, utilization of green synthesized nanomaterials has been widely growing on human body because of its special properties. With the increasing acceptance of nanoparticle approach for various clinical treatments, the biosafety and toxicological effects on the vital organs such as central nervous system, have received more concern. Main focus of this study was to evaluate acute exposure of n-butanol fraction of Prosopis cineraria (L.) Druce hydroethanolic extract (BuPC) and green synthesized zinc oxide nanoparticles of BuPC (ZnOPC) on spatial cognition behavior, and to assess underlying mechanism by estimation of enzymatic antioxidative status along with acetylcholinesterase (AChE) activity in mice brain. Strongest in vitro antioxidant and AChE inhibitory activity exhibiting fraction, BuPC, was examined for inhibition kinetic study by Lineweaver–Burk and Dixon plots. BuPC was further used for fabrication ZnOPC and characterized by UV-visible spectroscopy, Fourier Transform Infrared (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X ray (EDX) and Scanning Electron Microcopy (SEM) analysis. Old male swiss albino mice were randomly divided into seven groups and treated for 21 days. Subsequently spatial memory was determined by two behavioral models [Elevated plus maze (EPM) and Hebbs William maze (HWM)] and supernatant of brain homogenate was analyzed for enzymatic antioxidant level and AChE inhibitory activity. Zinc content of blood plasma and brain was estimated. Results showed prolonged transfer latency (TL) and time taken to reach reward chamber (TRC) by scopolamine was not ameliorated by the ZnOPC group, whereas BuPC group showed significant reduction in scopolamine induced increase in TL and TRC compared to control and scopolamine treated groups. ZnOPC alleviated enzymatic antioxidant activity and AChE as compared to donepezil and BuPC treated groups. Study concludes that ZnOPC attenuated spatial learning and memory by increase in oxidative stress and decrease in AChE activity at both dose levels. Our results suggest that BuPC exhibited a strong neuroprotective effect on cognitive deficit mice and it may be employed as a strong substance for the treatment of dementia whereas the green synthesized ZnOPC was not proficient to reverse the memory impairment induced by scopolamine.